Technology in Learning - van Wyk, Micheal (IntechOpen, 2023)
Rapid advancements in technology have had a significant impact on teaching and learning. Globally, we have experienced an increase in innovative pedagogies and disruptive learning spaces, which have transformed teaching and learning. Tremendous changes in educational innovations and methods have emerged over the last century, such as Open Educational Resources (OER), Mass Open Online Courses (MOOC), open resources, blended learning, and virtual reality (VR). Technology in Learning brings together in one single text the basic rudiments of technology integrated into teaching and learning in a manner that would assist the university postgraduate students, emerging researchers, and postdoctoral fellows who are engaged in the planning, designing, conducting as well as reporting on technology.